Phenomenological Study of Millennials' Assessment of Mubaligh in Indonesia - Pasaleron, Roni; Samsurizal, Samsurizal; Nadia, Ilmi (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2020)
This research aims to analyze Millennials' assessments of Mubalighs in Indonesia. This research uses a quantitative method with a phenomenological study with a survey approach, data sources were taken from one hundred and forty-one millennial respondents by distributing questionnaires. All survey results were then analyzed descriptively. The results of the research show that the millennials' assessment of the preachers they are interested in is the appearance aspect, namely simple appearance, the material aspect is material that is accompanied by clear arguments, the language aspect is light language and easy to understand, the delivery aspect is clear and firm, and the affordability aspect is accessible. on all social media. The results of this research can be used as initial data for future researchers in studying different issues related to this problem as well as various other issues that are relevant to this context.